INTERACTION OF MOLTEN URANIUM WITH ELECTRICAL PENETRATING TUBE OF A BOILING WATER REACTOR DURING SEVERE ACCIDENT - Rindi Wulandari; Sutanto Sutanto; Asril Pramutadi Andi Mustari (GANENDRA Majalah IPTEK Nuklir, 2020)
INTERACTION OF MOLTEN URANIUM WITH ELECTRICAL PENETRATING TUBE OF A BOILING WATER REACTOR DURING SEVERE ACCIDENT. Fukushima accident was the first severe accident of a BWR type which the core was melted leading to RPV failure at the bottom head. Regarding its complex structures of the bottom head, the scheme of failure is different from that of previous reactor severe accidents that ever happened (i.e. TMI-2 and Chernobyl accidents). There is a lot of penetration tubes through the bottom head leading to a complex interaction between corium and the structures. Eutectic reaction is possible to happen due to high temperature leading to a rapid failure of the RPV. Therefore, it is important to understand the phenomenon of interaction between corium and the structures. In this study, an interaction between molten uranium and structure of electrical tube, one of the penetration tubes, was analyzed by using MPS-LER method. Fluid dynamics of the MPS-LER simulation was validated by experiments of fluid flow by using water and oil.Calculation results of the fluid flow showed a good agreement with that of experiments.The MPS-LER was applied to calculate the penetration rate of molten uranium which flowed through the wall of the electrical tube at the bottom head of a BWR. The penetration rate was high due to eutectic reaction. The rate achieved 555.56 µm/s. Conservatively, it took less than 1 minute of time for the molten uranium to melt the tube wall with a thickness of 1.232 cm.